POLITENESS PRINCIPLES IN KARATE KID MOVIE - Mundiarti, Devi; Wulandari, Rifa Suci; Ro'is, Syamsuddin (STKIP PGRI Ponorogo Press, 2022)
Politeness is an important value in human behavior, includimg in communication. In It requires politeness to have a good relationship with each other. This research was aimed at analyzing the Politeness Principle based on Leech’s theory in Karate Kid movie by Harald Zwart. The design of the research was descriptive qualitative. The data were collected through documentation technique. The writer used descriptive qualitative analysis by Miles and Huberman. It included data display, reduction and verification. The results of analysis showed that there were 20 data as follows: two tact maxims, seven generosity maxims, three approbation maxim, one modesty maxim, two agreement maxims, and five sympathy maxim. There were six maxims in Karate Kid movie and generosity maxim was the dominant maxims used by the character in Karate Kid movie. By learning and understanding about politeness principles, the writer expects the reader will be more understand how to communicate to other people in their communication process because they have understood how to make communication comfortable.